Collection of Protestant Episcopal clergy correspondence - Dalrymple, Edwin A., 1818-1881.; Hobart, John Henry, 1775-1830.
Correspondence relating to the conduct of diocesan affairs in Alabama, Georgia, Illinois, Maryland, New York, North Carolina, and Virginia; essay on the necessity of the priesthood and other papers of John Henry Hobart, Bishop of New York; correspondence of Philander Chase, Bishop of Illinois and educator, who was instrumental in the founding and development of Kenyon College, Gambier, Ohio, and Jubilee College, Peoria, Ill.; and papers of William Ingraham Kip, first Bishop of San Francisco. Other correspondents include Bishops Alexander Viets Griswold, Levi Silliman Ives, James Kemp, Jackson Kemper, Charles Pettit McIlvaine, and William White.
Antiquarian, historian, and clergyman.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Chase, Philander, -- 1775-1852 -- Correspondence; Griswold, Alexander V. -- 1766-1843 -- Correspondence; Ives, L. Silliman -- 1797-1867 -- Correspondence; Kemp, James, -- 1764-1827 -- Correspondence; Kemper, Jackson, -- 1789-1870 -- Correspondence; Kip, William Ingraham, -- 1811-1893 -- Correspondence; McIlvaine, Charles Pettit, -- 1799-1873 -- Correspondence; White, William, -- 1748-1836 -- Correspondence; Episcopal Church -- Clergy; Episcopal Church -- Alabama; Episcopal Church -- Georgia; Episcopal Church -- Illinois; Episcopal Church -- Maryland; Episcopal Church -- New York (State); Episcopal Church -- North Carolina; Episcopal Church -- Virginia; Jubilee College; Kenyon College; Universities and colleges -- Illinois; Universities and colleges -- Ohio; Gambier (Ohio) -- History; Peoria (Ill.) -- History